Pemanfaatan Artificial Intelligence dalam Transformasi Pendidikan Islam di Era Digital - Tere Zahra Dzakirah; Rizky Iriana Zhafira Sugiarto; Moh. Faizin (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This article discusses the modernity of educational instruments, along with the phenomenon of technological progress, particularly the emergence of artificial intelligence (AI), and its implications for educators in the 21st century. Rapid advances in AI have led to fundamental shifts in teaching strategies and resources, shifting from traditional models to personalized and adaptive learning environments. Through automated assessments, curriculum customization, and the implementation of virtual assistants that enhance accessibility, artificial intelligence (AI) in education aims to improve efficiency and effectiveness. However, this modernity requires educators in the 21st century to change. Teachers now play the role of facilitators, designers of learning experiences, and mentors in ethics, in addition to being providers of knowledge. Teachers need to master AI literacy and focus on teaching students the four Cs of the 21st century: communication, creativity, critical thinking, and teamwork. The integration of AI raises ethical issues related to data privacy, the digital divide, and the dangers of plagiarism, but it also offers significant potential. Therefore, the effective integration of AI technology with irreplaceable human qualities is crucial for the success of contemporary educational technology. AI is an important tool for educators in the 21st century to develop a generation of technologically literate and moral individuals.